Endowing matrix-free carbon dots with color-tunable ultralong phosphorescence by self-doping. Issue 15 (30th March 2022) - Shi, Huixian; Niu, Zuoji; Wang, He; Ye, Wenpeng; Xi, Kai; Huang, Xiao; Wang, Hongliang; Liu, Yanfeng; Lin, Hengwei; Shi, Huifang; An, Zhongfu
Abstract : A new type of CDs with abundant carbonyl groups shows color-tunable ultralong phosphorescence from blue to red by self-doping, which was applied in information encryption and light detection. Abstract : Color-tunable ultralong phosphorescence is urgently desired in optoelectronic applications. Herein, we report a new type of full-color-tunable ultralong phosphorescence carbon dots (CDs) without matrix-assistance by a self-doping method under ambient conditions. The phosphorescence color can be rationally tuned from blue to red by changing the excitation wavelength from 310 to 440 nm. The CDs exhibit an ultralong lifetime of up to 1052.23 ms at 484 nm. From the experimental data, we speculate that the excitation-dependent multi-color phosphorescence is attributed to the presence of multiple emitting centers related to carbonyl units. Given the unique color-tunability of CDs, we demonstrate their potential applications in information encryption, light detection ranging from UV to visible light and LED devices. This finding not only takes a step towards the fundamental design of full-color emissive materials, but also provides a broader scope for the applications of phosphorescent materials.